Alopecia androgenética masculina de inicio precoz asociada a cáncer de próstata - Torres Cruz, Margarita Elizabeth (2017)
Context: male androgenetic alopecia is usual in men between 30 to 70 years of age; Its early presentation occurs in males under 31 years, related to androgens and inheritance, important factors in its etiopathogenesis. It has aesthetic repercussion, however, it is associated with cardiovascular risk and prostate cancer; It is postulated that the hormonal influence in male androgenetic alopecia favors the development of prostate cancer and determines its severity.Objective: To determine the association between early male alopecia and prostate cancer.Subjects and methods: men older than 18 years with confirmed prostate cancer; The control group consists of men older than 18 years without neoplasms with negative determination of prostate antigen. The study was carried out at the Carlos Andrade Marín HCAM Hospital, from May to September 2015.Results: relationship between androgenetic alopecia before 31 years and prostate cancer, with an OR of 4.25 (95% CI 1.7-10, p = 0.001). No statistical difference was observed between the severity of the prostate cancer and the clinical alopecic pattern.Conclusion: patients with early male androgenetic alopecia 31 years, have a higher risk of developing prostate cancer; Early androgenetic alopecia could be considered as an indicator of risk for prostate cancer, deserving its screening in patients with this early baldness.